Analisis Biaya Produksi dengan Metode Full Costing UMKM Bakso Sido Mandiri - Hanifah Silih Maulida; Indri Fitria Sari; Khalisa Radhia Tedjawati; Muhammad Ridho Rahman; Xaveriana, Fransiska; Intan Maulidhia; Tiar Lina Situngkir (LPPM POLITEKNIK LP3I BANDUNG, 2025)
Analysis for Micro, Small and Medium Enterprises or MSME meatballs using the Full Costing method aims to provide a comprehensive picture of efficiency and cost effectiveness in meatball production. This study was conducted by identifying the cost components involved, ranging from raw materials, labor, to overhead costs such as rent and utilities. This data was collected through interviews with MSME meatballs that were the objects of the study. The results of the analysis show that the application of the Full Costing method can help MSME in determining the right selling price and optimizing cost efficiency.